Molecular adjuvants based on nonpyrogenic lipophilic derivatives of norAbuMDP/GMDP formulated in nanoliposomes: stimulation of innate and adaptive immunity - Knotigová, Pavlína Turánek; Zyka, Daniel; Mašek, Josef; Kovalová, Anna; Křupka, Michal; Bartheldyová, Eliška; Kulich, Pavel; Koudelka, Štěpán; Lukáč, Róbert; Horáčková, Zuzana; Vacek, Antonín; Horynová, Milada Stuchlová; et al. (Pharmaceutical research, 2015)
PURPOSE: The aim of this work was to demonstrate an immunostimulatory and adjuvant effect of new apyrogenic lipophilic derivatives of norAbuMDP and norAbuGMDP formulated in nanoliposomes. METHODS: Nanoliposomes and metallochelating nanoliposomes were prepared by lipid film hydration and extrusion methods. The structure of the liposomal formulation was studied by electron microscopy, AF microscopy, and dynamic light scattering. Sublethal and lethal γ-irradiation mice models were used to demonstrate stimulation of innate immune system. Recombinant Hsp90 antigen (Candida albicans) bound onto metallochelating nanoliposomes was used for immunisation of mice to demonstrate adjuvant activities of tested compounds. RESULTS: Safety and stimulation of innate and adaptive immunity were demonstrated on rabbits and mice. The liposomal formulation of norAbuMDP/GMDP was apyrogenic in rabbit test and lacking any side effect in vivo. Recovery of bone marrow after sublethal γ-irradiation as well as increased survival of mice after lethal irradiation was demonstrated. Enhancement of specific immune response was demonstrated for some derivatives incorporated in metallochelating nanoliposomes with recombinant Hsp90 protein antigen. CONCLUSIONS: Liposomal formulations of new lipophilic derivatives of norAbuMDP/GMDP proved themselves as promising adjuvants for recombinant vaccines as well as immunomodulators for stimulation of innate immunity and bone-marrow recovery after chemo/radio therapy of cancer.
Keywords: Adaptive Immunity; myši; Microscopy, Electron, Transmission; Molecular Structure; přirozená imunita; Microscopy, Electron, Scanning; analýza přežití; Radiation Injuries, Experimental; Female; nanočástice; Microscopy, Atomic Force; mikroskopie elektronová rastrovací; rekombinantní proteiny; acetylmuramyl-alanyl-isoglutamin; adaptivní imunita; králíci; Immunity, Innate; ženské pohlaví; Mice, Inbred ICR; mikroskopie atomárních sil; antigeny fungální; proteiny tepelného šoku HSP90; Animals; Mice; zvířata; liposomy; adjuvancia imunologická; experimentální radiační poranění; Drug Carriers; Survival Analysis; nosiče léků; Acetylmuramyl-Alanyl-Isoglutamine; Rabbits; HSP90 Heat-Shock Proteins; Liposomes; Recombinant Proteins; Antibodies, Fungal; Antigens, Fungal; myši inbrední ICR; molekulární struktura; Nanoparticles; transmisní elektronová mikroskopie; protilátky fungální; Adjuvants, Immunologic